LACTOBACILLUS PLANTARUM FROM BERRIES OF GRAPE CULTIVATED IN THE SOUTH OF UKRAINE - А. Г. Мерліч; В. О. Iваниця; Н. В. Коротаєва; М. А. Златогурська; Н. Ю. Васильєва; Д. О. Бабенко; Н. В. Ліманська (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2013)
The aim of the investigation was the isolation of Lactobacillus plantarum from berries of grape and the study of their genetic diversity. Materials and Methods. Lactic acid bacteria were isolated from berries of 14 grape cultivars grown in the south of Ukraine. PCR-assay and RAPD-PCR were used for L. plantaruт identification and the study of their diversity. The reconstruction of phylogenetic tree of the studied strains was carried out with Matlab 7.0 program. Results. Lactobacilli have been isolated from 7 samples of must among 14 of the tested grape cultivars. 80% of the studied strains belonged to L. plantarum species. Groups of genetic similarity between L. plantarum strains have been revealed. In the phylogenetic tree four clusters of the strains grouped by their similarity were formed. The mentioned results allowed to conclude that L. plantarum strains from must of grape of different cultivars and territories of grape cultivation could show the genetic similarity. Opposite, some L. plantarum strains from one source of origin could demonstrate the genetic diversity.